El enfoque restaurativo en el Sistema Penal Juvenil, al amparo del principio de especialidad - García Tapia, Doménica Mayerly (2024)
This Curricular Integration Work was carried out with the intention of decrease the wave of the eminent delinquency rates that are generated repeatedly by the young sector. In this sense, the appropriate and timely detection of the deficiencies present in the Administration de Justicia Juvenil Specialized supports the judicial sphere and the agencies that work together with it, to act in accordance with the constitutional requirements, which is why it is essential to know and determine how the restorative mechanisms and the regulatory precepts of the specialty, influence the effective reeducation of adolescent offenders. Within this context, the current study compiles various research resources, including a wide range of bibliographic references in digital and physical format, in addition to national and comparative legislation currently in force. In a similar vein, different methodological approaches were used including analytical, synthetic, inductive, deductive and statistical. Finally, in accordance with the nature of the doctrinal research, the documentary technique was used as the most appropriate tool to understand the extent of the theoretical ideas, their limitations and scope, which were solidly supported and complemented by interviews with various experts in the legal field and which were considered taking into account their expertise in the field; such inputs allowed us to strengthen the appreciation of the transcendence of the restorative approach and the fundamental categorical of the principle of specialty. These precedents made it possible to carry out a condensed analysis whose bases were solidified in doctrine, national, supranational and comparative legislation, casuistry and experience, which considerably strengthened the discussion, allowing us to extract a series of significant evaluations in relation to how the specialization of the penal system makes the implementation of restorative programs and the achievement of rehabilitative purposes in the context of juvenile justice viable. In addition, we were able to derive specific recommendations from the research, which we hope will be fundamental in the future and contribute to maintain a more organized social structure free of delinquent circles, emphasizing mostly the juvenile sector.